Ethics of Scientific Research and Problematic of Documenting in Social and Human Sciences - Fatima zahra Teniou; Moufida Tair (Social Empowerment Journal, 2019)
Scientific research in the humanities and social sciences, as well as the exact sciences, requires respect for the structure of science established by the frequent critical work of epistemology to allow for a set of ethical values and principles for those who practice them. Those who think that the research process is not merely understanding a set of principles and procedures related to problem identification, preparation of research design, data collection, statistical handling, , But there is a set of ethical standards that accompany each of these stages. The researcher must be aware of these standards and values ​​as he deals with human rights and dignity, which must be preserved and maintained from any apparent damage or enduring, and one of the most important aspects of respect for research ethics and the documentation process and the more severe problems in the field of human and social sciences that suffer In which the researcher is more than any other in investigating the scientific credibility in the process of documentation, and in view of these data we try through this intervention to address the ethics of scientific research and documentation by highlighting its moral, methodological and scientific conditions, all of which are mutually supportive to preserve his identity and status. Therefore, we will try to answer the following questions: What do we mean by scientific research in the field of human and social sciences? What are the qualities of the researcher? What is search ethics? What are the correct authentication procedures? What is the scientific secretariat?